Oral Opportunistic Infection Induced by Stress and Silent Type 2 Diabetes Mellitus in Young Adult Patient: A Case Report - Karina D; Heldayani I; Hidayat W (International Medical Case Reports Journal)
Dhini Karina,1 Iin Heldayani,1 Wahyu Hidayat2 1Oral Medicine Residency Program, Faculty of Dentistry, Universitas Padjadjaran, Bandung, Indonesia; 2Department of Oral Medicine, Faculty of Dentistry, Universitas Padjadjaran, Bandung, IndonesiaCorrespondence: Wahyu Hidayat, Department of Oral Medicine, Faculty of Dentistry, Universitas Padjadjaran, Jalan Sekeloa Selatan I, Bandung, 40132, Indonesia, Tel +6287822404343, Email wahyu.hidayat@fkg.unpad.ac.idIntroduction: Opportunistic infections (IO) are infections of microbiota (fungi, viruses, bacteria, or parasites) that generally do not cause disease but turn into pathogens when the body’s defense system is compromised. This can be triggered by various factors, one of which is due to a weakened immune system due to Diabetes Mellitus (DM), which increases the occurrence of opportunistic infections, especially in the oral cavity. Fungal (oral candidiasis) and viral (recurrent intraoral herpes) infections can occur in the oral cavity of DM patients. Recurrent intraoral herpes (RIH) is generally a recurrent herpes virus infection with one of the triggers being stress.Objective: To determine the role of stress and silent type 2 DM and which is thought to trigger opportunistic infections in oral cavity.Case: A 34-year-old man was referred with complaints of white patches in the mouth, sore throat a difficulty swallowing and opening the mouth. Extraoral examination, yellow-black crusts were found on the lips. Intraoral and tongue examination revealed white plaque that could be scraped off, and a mouth mirror was attached. The hard palate showed vesicles that spread to the soft palate. Laboratory tests were abnormal for blood sugar, anti-HSV-1 IgG, and presence of hyphae. Mild anxiety and moderate stress. The working diagnosis was pseudomembranous candidiasis RIH, exfoliative cheilitis, and xerostomia. Differential diagnosis was erythema multiforme.Case Management: Pharmacologic dental management was fluconazole injection, acyclovir, NaCL 0.9%, chlorine dioxide mouthwash, and petroleum jelly. Non-pharmacologic therapy dental included oral hygiene instruction and education on oral therapy and referral to the internal medicine clinic for DM management. After two weeks of collaborative treatment between oral medicine and internal medicine, there was significant improvement.Conclusion: Silent type 2 DM and stress can cause a decrease in the immune system, triggering opportunistic infections, namely RIH and candidiasis.Keywords: diabetes mellitus, immunosuppression, oral opportunistic infections, stress